The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.7124/bc.000989
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of the recombinant human leukemia inhibitory factor in mice with an experimental cuprizone model of multiple sclerosis: possible mechanisms

Abstract: To investigate the effects of the rhLIF recombinant human leukemia inhibitory factor on the structural and functional changes in the central nervous system in the cuprizone-induced experimental model of multiple sclerosis in mice and to evaluate the involvement of the brain macrophages, T-lymphocytes and antioxidant enzymes in the observed rhLIF effects. Methods. Young 129/Sv mice were fed with the cuprizone neurotoxin daily for three weeks. rhLIF was injected daily (50 μg/kg) after seven days of the cuprizone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(20 citation statements)
references
References 27 publications
(40 reference statements)
4
15
0
1
Order By: Relevance
“…Positive changes in the behavior of mice with a cuprizone diet after the transplantation of UC-MMSCs can most likely be associated with their anti-inflammatory properties, in particular, the synthesis of IL-10, a decrease in the manifestation of active gliosis in the brain [25,31]. According to our data, in mice with a cuprizone diet, the number of active macrophages in the brain decreases under the influence of cytokines with an anti-inflammatory effect [28].…”
Section: The Effects Of Uc-mmscs and Melatonin In Aged Mice With Demyelinating Diseasessupporting
confidence: 51%
See 1 more Smart Citation
“…Positive changes in the behavior of mice with a cuprizone diet after the transplantation of UC-MMSCs can most likely be associated with their anti-inflammatory properties, in particular, the synthesis of IL-10, a decrease in the manifestation of active gliosis in the brain [25,31]. According to our data, in mice with a cuprizone diet, the number of active macrophages in the brain decreases under the influence of cytokines with an anti-inflammatory effect [28].…”
Section: The Effects Of Uc-mmscs and Melatonin In Aged Mice With Demyelinating Diseasessupporting
confidence: 51%
“…UC-MMSCs of the 2 nd passage were injected once into the tail vein on the 10 th day of the cuprizone diet at a dose of 5•10 5 cells per 50 μL in saline. It was found that after 8-10 days of cuprizone diet in the brain of mice of different lines, including 129/Sv, there was oligodendrocyte apoptosis and changes in the structure of neurons and behavior [24,28]. In addition, the therapeutic effect of human bone marrow-derived MMSCs after transplantation into mice taking cuprizone has been shown [29].…”
Section: Animalsmentioning
confidence: 99%
“…hMMSCs were injected once into the tail vein of mice on the 10th day of cuprizone diet at a dose of 5•10 5 cells per 50 μl of saline. It was found that after 8-10 days of cuprizone treatment there were signs of demyelination and apoptosis of oligodendrocytes in the brain as well as changes in the structure of neurons and in the behavior of mice [1,20].…”
Section: Methodsmentioning
confidence: 99%
“…Factors of oxidative stress and antioxidant protection were determined, as described previously [12,20]. The malondialdehyde (MDA) content in brain homogenate was determined by colour intensity of the trimethine complex formed between thiobarbituric acid and MDA.…”
Section: Methodsmentioning
confidence: 99%
“…При этом мы не исключаем возможности получения отдаленного нейропротекторного эффекта rhIL-10 в дозе 5 мкг/кг у мышей с купризоновой моделью демиелинизации. Подобный эффект у мышей с этой моделью мы уже наблюдали у цитокина с нейротропными свойствами -лейкемия ингибиторного фактора [31].…”
Section: Discussionunclassified